Bonan Youang and Terrinalum: The Ethnogeology of Ballaarat’s Living Landscape - David S. Jones (Geographies, 2023)
Ethnogeology offers a longitudinal history of the formation of landscapes though the lens of First Nations Peoples. Significantly, it offers an insight into landscape change and geographical formation as consequence of geological events, climate shift (change), and consequential human resilience and adaptation strategies. This article considers a cultural landscape near Ballaarat (Ballarat) in Australia and its geological omnipresence in the eyes of the First Nations’ Wadawurrung People. The features, two extinct volcanoes—Bonan Youang (Mt Buninyong) and Terrinalum (Mt Elephant)—and a connection tract, offer high cultural values to the Wadawurrung People in addition to serving as key contemporary mental and orientation landmarks arising from their roles in the locality’s pastoral, goldmining, and suburbanisation colonisation phases.